Assessing the economic factors affecting road accidents in the Mpumalanga Province - Makhubela, T.R. (North-West University (South Africa), 2021)
Purpose: The specific purpose of this paper is to assess the impact of economic factors on road accidents in the Mpumalanga Province, for the period 2010 to 2019. Methodology: A quantitative research method was used to investigate the influence of economic factors on road accidents in the Mpumalanga Province. Secondary data pertaining to the Gross Domestic Product per capita, unemployment, inflation rate, motorisation, road infrastructure investment, and the number of road accidents, were collected from Municipal Annual Reports, Statistics South Africa Reports, and South African Reserve Bank (SARB) Bulletins, through content analysis. Data was analysed using descriptive and inferential statistics. In addition, a simple regression analysis was performed to confirm the correlation between economic factors and road accidents in the Mpumalanga Province, for the period 2010 to 2019. Findings: Through a simple regression analysis, the results showed a positive correlation between unemployment rates, inflation rates, motorisation, and road accidents in the Mpumalanga Province. However, the Gross Domestic Product per capita and the level of road infrastructure investment showed a negative correlation with road accidents. Research limitations: Like other similar studies, this investigation also had its own limitations. Secondary data pertaining to economic factors and road accidents was collected for the Mpumalanga Province only, even though South Africa has nine provinces. Therefore the results of this study may not be generalised across the country. Value: The findings and recommendations of this study will allow provincial governments to formulate and implement economic policies that will boost the Gross Domestic Product per capita at provincial level. This will translate into a good road network, resulting in reduced road accidents. Moreover, an in-depth understanding of the impact of economic factors on road accidents in Mpumalanga will provide a basis for economic growth and development policies that will address other socio-economic issues in the near future. Furthermore, the research findings will also provide a platform for further studies by academics in the field of Economic Management Sciences.
MBA, North-West University, Potchefstroom Campus
Keywords: Economic variables; motorisation; Gross Domestic Product per capita; inflation rate; Consumer Price Index; road infrastructure investment; road accidents and unemployment